Dennd1a, a susceptibility gene for polycystic ovary syndrome, is essential for mouse embryogenesis. Issue 5 (2nd April 2019) - Shi, Jingjing; Gao, Qing; Cao, Yongzhi; Fu, Jiang
Abstract: Background: The DENND1A has been identified as a guanine nucleotide exchange factor for small GTPase Rab35, which functions in endocytic trafficking to mediate the recycling of selective cargos. Genetic alterations within the DENND1A gene have been implicated in human disease such as polycystic ovary syndrome (PCOS). However, the role of DENND1A in developmental and reproductive processes is largely unknown. Results: Using Dennd1a gene knockout mice, we uncovered that homogeneous Dennd1a−/− mutants died around embryonic day (E) 14.5. The brain of Dennd1a−/− embryos exhibited defects, partially attributed to the dysregulation of cell division and survival in the telencephalon. The transcription of Fgf8 mRNA was ectopically elevated in the dorsal midline of telencephalon, concomitant with a decrease of active β‐catenin and Axin2 in the brain of Dennd1a−/− embryos. During liver morphogenesis, the ablation of Dennd1a impaired hepatic cell proliferation, the differentiation of hepatocyte, and hepatic hematopoiesis. In addition, loss of Dennd1a also affected the development of primordial germ cells. Conclusions: We demonstrate that Dennd1a, a susceptibility gene for PCOS, is essential for embryogenesis, probably through the mediation of endocytic recycling of selective cargos that are involved in cell signaling crucial for the development of multiple embryonic organ systems. Key Findings: Dennd1a is required for brain morphogenesis. Dennd1a is necessary for hepatic development and hematopoiesis. Dennd1a is involved in development of primordial germ cells (PGCs).